2020
DOI: 10.1051/e3sconf/202017504001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding a natural feed additive on the performance of broiler chickens

Abstract: Natural feed additive is made on the basis of bottom sediments of the steppe reservoirs of the Krasnodar Territory and is a dry powder of a grayish tint. Mineralization of local bottom sediments is 6.5 g / kg, calcium content is 29.7 g / kg, macronutrients from 1.04 to 25.8 g / kg, trace elements from 0.03 to 0.7 g / kg. The medium reaction is from neutral to slightly alkaline. Using sapropel feed additives (SFA), it was possible to increase the gross live weight gain of broiler chickens by 1.7-2.0% while redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Sapropel, depending on the depth, has different agrochemical and physical properties [59]. Therefore, several research studies have tested the possibilities of supplementing complex poultry feed with organic sapropel to increase feed absorption efficiency and develop natural, safe and locally-sourced feed for young poultry [28,29,38,60,61]. Diets for broiler chickens should aim to achieve a leaner carcass, reducing the feed conversion ratio, and increasing weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Sapropel, depending on the depth, has different agrochemical and physical properties [59]. Therefore, several research studies have tested the possibilities of supplementing complex poultry feed with organic sapropel to increase feed absorption efficiency and develop natural, safe and locally-sourced feed for young poultry [28,29,38,60,61]. Diets for broiler chickens should aim to achieve a leaner carcass, reducing the feed conversion ratio, and increasing weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that the introduction of 3 to 5 % of dry sapropel into the diet of chickens not only reduced feed costs, but also increased their live weight and survival rate (Pozdnyakova et al, 2019). The use of sapropel feed additives (SFA) allowed the gross live weight gain of broiler chickens to be increased by 1.7-2.0% while reducing feed costs per 1 kg of gain by 0.5% (Yurina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sapropel is composed of the remains of animals and plants living in freshwater bodies; it consists of organic substances and an admixture of sand, clay, and carbonates that make up 5-85% of the mass. In some countries, significant research has been conducted on the extraction and chemical composition of sapropel, finding that sapropel represents more than 30 macro and microelements [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%